2018
DOI: 10.4172/neuropsychiatry.1000397
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Brazilian Version of WHODAS 2.0 in Patients with Mental Disorders: Should the 12-Item Scale be an Alternative to 36-Item Scale in DSM-5?

Abstract: The World Health Organization Disability Assessment Schedule (WHODAS) 2.0 Brazilian version was self-applied in 500 psychiatric and 50 non-psychiatric patients in an outpatient medical centre. The instrument was reapplied in 50 psychiatric patients whose treatment with psychotropics was not altered, and in 100 whose it was altered. Confirmatory factor analysis confirmed the theoretical dimensional model proposed by the WHO for the WHODAS 2.0 36-item scale, and a simpler alternative model for the WHODAS 2.0 12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
(29 reference statements)
2
3
0
Order By: Relevance
“…Additional research within a larger sample is needed to confirm findings. We note, however, that these findings are very similar to what has been reported for both clinical and nonclinical populations [e.g., Brasil & Correr, ; Chiu et al, ; Garin et al, ; Luciano et al, ; Moen et al, ; Üstün et al, ]. Fifth, while we did include an independent clinician rating of social functioning, future studies may also wish to include reports from partners and significant others to determine the relationship between self‐report assessment and significant other assessments.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Additional research within a larger sample is needed to confirm findings. We note, however, that these findings are very similar to what has been reported for both clinical and nonclinical populations [e.g., Brasil & Correr, ; Chiu et al, ; Garin et al, ; Luciano et al, ; Moen et al, ; Üstün et al, ]. Fifth, while we did include an independent clinician rating of social functioning, future studies may also wish to include reports from partners and significant others to determine the relationship between self‐report assessment and significant other assessments.…”
Section: Discussionsupporting
confidence: 89%
“…The internal consistency analysis showed that the summary and different domain scores of the 36-item WHODAS II present adequate internal consistency (α > 0.7). Similar Cronbach's values have been obtained in previous studies with the 36-item version in patients with ASD [Schmidt et al, 2015], bipolar [Guilera et al, 2015], depression [Chwastiak & Von Korff, 2003;Luciano et al, 2010], schizophrenia [Guilera et al, 2012], or other mental disorders [Brasil & Correr, 2018]. All items (except item 4.5 "sexual activity") exhibited satisfactory correlation with their respective domains and summary scores, indicating that the WHODAS-II items can discriminate high-scoring individuals from a lower scoring individual.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The 12-item version is short, simple, easy to administer in both clinical and general population settings and takes about 5 to 20 minutes to complete. The 12-item version is preferred over the 36-item version and reported to have good internal consistency, discriminant validity, construct validity [4][5][6], and considered more responsive than the 36-item version [7].…”
Section: Introductionmentioning
confidence: 99%
“…At the time of applying BariTest, 175 patients also received two other questionnaires: the WHODAS 2.0 (Annex 1), which is a self-administered questionnaire that measures functionality and disability related to any disease or health status, avoiding the researcher's bias, and the Obesity -related Problems Scale (OP) (Annex 2), which is a scale of outcomes reported by patients that measures the impact of excess weight on psychosocial functioning. These instruments were chosen because they have been validated 4,5 for the Brazilian population with obesity to measure psychological well-being.…”
Section: Introductionmentioning
confidence: 99%